Determination оf the aromatic hydrocarbons in petroleum products - Аміруллоєва, Наталя Валеріївна (Eastern-European Journal of Enterprise Technologies, 2015)
Comparative assessment of modern physicochemical methods for determining the aromatic hydrocarbons in diesel fuel was performed. In order to control the quality and the environmental characteristics, the structural-group and fractional compositions of the sample of commercial diesel fuel were identified. Pre-separation of the diesel fuel containing these compounds was carried out by column chromatography. The qualitative and quantitative analysis of the diesel fuel and the resulting fractions was conducted by mass spectrometry and gas-liquid chromatography. Analysis of these products by UV-spectroscopy allows direct determination of aromatic hydrocarbons with the satisfactory convergence of the results. On the example of diesel fuel, a systematic approach in determining the group composition of multi-component objects was shown. A set of the methods applied can be used for identifying the organic substances of unknown composition, solving scientific and technical tasks, such as qualitative and quantitative analysis of commercial petroleum products, monitoring of natural objects. The complex of methods and systematic approach for investigating complex mixtures allows to increase the reliability and validity of the results.